2019
DOI: 10.1177/0020764019882728
|View full text |Cite
|
Sign up to set email alerts
|

Is unemployment less important than expected for suicide attempted in developing regions? Occupational profile of suicide attempts in Jujuy, north westernmost Argentina

Abstract: Background: Mental health practices consider unemployment as a suicide main risk factor, based on models built for populations of developed countries. Aim: This study assesses the association between the occupational risk factor and suicidal behaviors, by considering sex, age and temporal distribution, in a Latin American Andean population from north westernmost Argentina. Methods: Data include 481 suicide attempt cases assisted by emergency service psychologists at a head hospital in the Jujuy Province, north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…One study reported a significant positive relationship between rainfall values and suicide rates among females in Taiwan (Tsai, 2010). In a study, López Steinmetz et al (2020) reported that unemployment is not associated with suicidal behavior in Andean populations in north westernmost Argentina (López Steinmetz et al , 2020). A study by López Steinmetz et al (2020) on the suicide mortality rates for a period from 2003 to 2013 in rural regions of Argentinean Andes showed that lithium (and not altitude) was positively correlated with suicide mortality (Steinmetz et al , 2021); however, according to another study, lithium would be negatively related to suicide rates in low-altitude areas, whereas it would be positively associated with high altitude (Helbich et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a significant positive relationship between rainfall values and suicide rates among females in Taiwan (Tsai, 2010). In a study, López Steinmetz et al (2020) reported that unemployment is not associated with suicidal behavior in Andean populations in north westernmost Argentina (López Steinmetz et al , 2020). A study by López Steinmetz et al (2020) on the suicide mortality rates for a period from 2003 to 2013 in rural regions of Argentinean Andes showed that lithium (and not altitude) was positively correlated with suicide mortality (Steinmetz et al , 2021); however, according to another study, lithium would be negatively related to suicide rates in low-altitude areas, whereas it would be positively associated with high altitude (Helbich et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies supporting such results have been conducted in developed countries. In this regard, it is important to bear in mind that we have previously discussed on dissimilar patterns existing in mental health-related problems between populations from developed and developing countries ( López Steinmetz, 2015 , 2017b ; López Steinmetz et al., 2019 ). For instance, we have demonstrated that there are no sex differences in suicide attempters from the north westernmost of Argentina ( López Steinmetz, 2017a ).…”
Section: Discussionmentioning
confidence: 99%